A critical analysis of the Physical Education curriculum in the Czech Republic - Vlcek, Petr (Logos Verlag Berlin, 2019)
This monograph reviews the PE curriculum in the Czech Republic. It presents research into the quality of the Czech PE curriculum and makes recommendations regarding its redesign. It targets the scientific community and experts in the field and seeks to enrich international research on the PE curriculum and update the knowledge base of curriculum study. The text should be of general value and of particular relevance to any future change of the PE curriculum in the Czech Republic. The first section of the monograph focuses on curriculum theory; the term `curriculum' is defined and its structure described, some basic terminology regarding curriculum change is explained, some aspects of a quality curriculum are discussed, and the various concepts that can underpin a PE curriculum are identified. The history of PE in the Czech Republic sets the scene for the research section of the monograph, which describes predominantly the author's PE curriculum research over the last decade. In the following chapters the current PE curriculum in the Czech Republic is reviewed based on research findings and recommendations made regarding the revision of the PE curriculum in the Czech Republic. Finally, the dichotomies that characterize research in this area are discussed.